Whey-reconstituted milo for finishing beef heifers - Bolsen, K.; Grimes, C.; Mickelson, R. (Kansas State University. Agricultural Experiment Station, 2011)
Three milo treatments were evaluated in finishing rations for heifers: dry-rolled, reconstituted with water, and reconstituted with whey. Reconstituting milo with water or whey did not increase weight gain or efficiency of heifers over that of heifers fed dry-rolled milo. The slowest and least efficient gains were produced by the water-reconstituted milo. Performances were similar for the dry-rolled and whey-reconstituted milo treatments.
1776-1976 "Buffalo to Beef" is known as Cattlemen’s Day, 1976
Keywords: Beef; Milo; Heifers